Customer Relationship Management (CRM) Strategy in Increasing Customer Loyalty at Amo_Nailart - Agnes, Agnes; Pasaribu, Veta Lidya Delimah (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2024)
This study aims to analyze the Customer Relationship Management (CRM) strategy implemented by Amo_nailart, an MSME in the field of nail art, in increasing customer loyalty. A quantitative approach with a descriptive method was used in this study. Data were collected through questionnaires to three Amo_nailart customers, interviews with the owner, and documentation studies. The results showed that Amo_nailart has implemented several CRM strategies, such as recording customer data, communicating via WhatsApp, and providing member cards. Correlation analysis showed a significant positive relationship between the implementation of CRM strategies and the level of customer loyalty (0.85). Other factors that influence customer loyalty are service quality, therapist expertise, price, location, and waiting time. Although the CRM strategy implemented is still simple and has some limitations, such as manual data recording and lack of social media utilization, the strategy has been proven to contribute positively to customer loyalty. It is recommended that Amo_nailart adopt a digital CRM system, utilize social media optimally, develop a more comprehensive loyalty program, and provide training to employees regarding the implementation of CRM.